2008
DOI: 10.1186/1472-6750-8-97
|View full text |Cite
|
Sign up to set email alerts
|

Single-chain Fv phage display propensity exhibits strong positive correlation with overall expression levels

Abstract: BackgroundSingle chain Fvs (scFvs) are widely applied in research, diagnostics and therapeutic settings. Display and selection from combinatorial libraries is the main route to their discovery and many factors influence the success of this process. They exhibit low thermodynamic stability, resulting in low levels of premature cytosolic folding or aggregation which facilitates sec YEG-mediated translocation and phage in E. coli. However, there is little data analysing how this is related to and influenced by sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…To name a few: biases begin already during library construction (Sblattero and Bradbury, 2000;Holt et al, 2000) as a result of PCR-based bias in amplification of different templates, during the subsequent PCR amplifications used for assembly of scFvs and due to the fact that actual library size falls short of covering all possible combinations of V H and V L domains present in the cDNA. Second, some scFvs display better on phage than others (Malone and Sullivan, 1996;Pavoni et al, 2007;Scott et al, 2008), as is shown in our evaluation of the three HTS-chosen clones that displayed very poorly on phage. Third, the affinity selection process itself is very sensitive to varying conditions and experimental variations (Hoogenboom et al, 1999;de Wildt et al, 2000;Smith et al, 2005), frequently leading to different antibodies being isolated for a particular antigen by different individuals or even by the same individual under slightly varying experimental conditions.…”
Section: Discussionsupporting
confidence: 51%
“…To name a few: biases begin already during library construction (Sblattero and Bradbury, 2000;Holt et al, 2000) as a result of PCR-based bias in amplification of different templates, during the subsequent PCR amplifications used for assembly of scFvs and due to the fact that actual library size falls short of covering all possible combinations of V H and V L domains present in the cDNA. Second, some scFvs display better on phage than others (Malone and Sullivan, 1996;Pavoni et al, 2007;Scott et al, 2008), as is shown in our evaluation of the three HTS-chosen clones that displayed very poorly on phage. Third, the affinity selection process itself is very sensitive to varying conditions and experimental variations (Hoogenboom et al, 1999;de Wildt et al, 2000;Smith et al, 2005), frequently leading to different antibodies being isolated for a particular antigen by different individuals or even by the same individual under slightly varying experimental conditions.…”
Section: Discussionsupporting
confidence: 51%
“…They were also compared in terms of overall expression levels, soluble localisation to the periplasm and culture supernatant as well as their propensity for display on phage, as reported separately (Scott et al, 2008). …”
Section: Resultsmentioning
confidence: 99%
“…The zz-phage were constructed based on a phagemid/helper phage system utilizing a modified pCantab6 amp r phagemid (McCafferty et al 1996) and were rescued using M13KO7 helper phage. The pCantab6 phagemid p3 gene was genetically modified to contain the zz domain near the amino terminus after the leader signal sequence for SecYEG mediated periplasmic translocation (Scott et al 2008). The insert containing the zz domain was obtained by PCR of a TAP tag insertion cassette derived from pFA6a-TAP-His3MX (Ghaemmaghami et al 2003) using the following primers (zz for: ACAACTG-CAGGTGGACAACAAATTCAACAAAGAACAAC; zz rev: TATTGC GGCCGCCTGATGATTCGCGTCTACTTTCG) to generate PstI and NotI restriction sites, respectively.…”
Section: Genetic Engineering Of Zz-phagementioning
confidence: 99%